A Description of Female Pesantren Students Subjective Well-Being - Mauliddina Qurrota A’yun; Fatwa Tentama; Nina Zulida Situmorang (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2018)
The present study aimed to explore the depiction and the factors of subjective wellbeing of santriwati pondok pesantren. The present study was categorized into phenomenological qualitative study. The subjects of the study were female adolescents aged (15-18) who were the fourth year santriwati, there were 6 people and three significant persons who were selected by using purposive sampling.  The data were collected using a semi-structured interview. The data were analyzed by transcribing the interview, coding, and interpreting as well as drawing the conclusion. Based on the study, cognitive component named santriwati's life satisfaction that was expressed by gratitude and positive relation with their friends and pondok pesantren environment. The affective component was in the form of positive and negative affect. Positive affect such as being comfortable with the facilities in pondok pesantren, being happy when completing memorization target, and being happy for mutual strengthening among friends in pondok pesantren. The negative affect such as being sad to be far away from the parents and pressure due to school activities and pondok pesantren activity.   The factors affecting subjective well-being of santriwati Pondok pesantren were self-esteem, personal control, extroversion, optimism, positive social relationship, life meaning and goal, as well as idolized model or figures. The result of the study can be used as consideration for the school counselor in providing assistance and simple skill regarding well-being to the subjects in Pondok pesantren.